2021
DOI: 10.17759/cpse.2021100106
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Anti-Doping Policy Legitimacy in the Social Psychology of Sports

Abstract: Anti-doping represents a global system where an athlete is in the center of a control and regulations. The perception of legitimacy is important for compliance with rules and regulation within the anti-doping system. However, the concept of legitimacy in anti-doping is not sufficiently defined, which makes it difficult to develop psychodiagnostic tools for its assessment within the framework of relevant psychological theories. The aim of this study is to review psychological literature on legitimacy perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Recently, it has been shown that athletes’ perceptions of the importance of clean sport and clean sport values can vary across different countries ( Woolway et al, 2021 ). As values are linked to doping behaviour ( Ring et al, 2020 ), it could be that culture may also play a role in engagement with, and acceptance of whistleblowing in sport ( Keenan, 2007 ; Bondarev et al, 2021 ). Culture refers to the individual’s characteristics that based on the perception of rules, norms, roles, and values, influenced by various societal levels (e.g., country, race, occupation etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that athletes’ perceptions of the importance of clean sport and clean sport values can vary across different countries ( Woolway et al, 2021 ). As values are linked to doping behaviour ( Ring et al, 2020 ), it could be that culture may also play a role in engagement with, and acceptance of whistleblowing in sport ( Keenan, 2007 ; Bondarev et al, 2021 ). Culture refers to the individual’s characteristics that based on the perception of rules, norms, roles, and values, influenced by various societal levels (e.g., country, race, occupation etc.…”
Section: Discussionmentioning
confidence: 99%